Pengaruh kompetensi kecerdasan emosi terhadap prestasi kerja guru di Sekolah Menengah, Sarawak - Lester Surai; Muhamad Suhaimi Taat (Universiti Malaya, 2024)
This study aimed to identify the influence of emotional intelligence on teachers work performance among secondary school teachers in Sarawak, Malaysia. The nonexperimental study utilised the survey method by combining several variable sampling techniques to obtain samples. Data was collected through a set of adapted questionnaires administered to 363 teachers. Descriptive analysis shows emotional intelligence competence and teachers work performance being practised at a high level. One-way ANOVA test results show that there is a significant difference in emotional intelligence competence and teachers work performance based on teaching experience. Multiple regression analysis also shows that there is a significant influence of emotional intelligence competence towards teachers work performance. The findings show that the overall contribution predicted by emotional intelligence competence towards teachers work performance is 54.4 percent. Implications and recommendations for further studies are also discussed.